Efficient and stable photoelectrochemical hydrogen generation using optimized colloidal heterostructured quantum dots. (January 2021) - Zhang, Hui; Besteiro, Lucas V.; Liu, Jiabin; Wang, Chao; Selopal, Gurpreet S.; Chen, Zhangsen; Barba, David; Wang, Zhiming M.; Zhao, Haiguang; Lopinski, Gregory P.; Sun, Shuhui; Rosei, Federico
Abstract: Colloidal semiconductor quantum dots (QDs) are considered as promising building blocks to fabricate efficient and stable optoelectronic devices, thanks to their size/shape/composition-dependent electronic and optical properties based on the quantum confinement effect. However, inadequate light absorption and undesirable charge recombination events still limit the efficiency and long-term stability of solar energy to fuel conversion in QD-based photoelectrochemical (PEC) cells. In this work, we engineer the optoelectronic properties and band alignment in colloidal heterostructured CdS/CdSe core/shell QDs by tuning the shell thickness. Starting with a 3.0 nm CdS QD core (in diameter), we investigate the changes in structural and optical properties as a function of CdSe shell thickness (0.6–1.9 nm). We show that the optimization of the shell thickness can significantly broaden the light absorption range towards longer wavelengths and enhance the rate of photoelectron separation and transport in photoanodes made of QDs sensitized TiO2 mesoporous film. Complemented by theoretical modeling, we find that the band alignment in this heterostructured system can be engineered from quasi type-II (electrons are localized over the entire QDs but holes are mostly delocalized in shell) to inverted type-I (both electrons and holes are largely delocalized in shell) by changing the shell thickness. As a proof-of-concept, employing QDs with optimal shell thickness of 1.6 nm together with carbon nanotube doped TiO2 as photoanode in PEC cells, we obtained a very high photocurrent density of ~ 16.0 mA/cm 2 (at 0.9 V vs. the reversible hydrogen electrode, RHE), which is the highest value ever reported for PEC cells based on CdS/CdSe QDs. We also observed an excellent long-term stability (maintaining 83% of its initial value after four hours) under one sun illumination (AM 1.5G, 100 mW/cm 2 ). These results indicate that optimizing the design and band engineering of heterostructured core/shell QDs is a facile and efficient approach to enhance the performance of QDs-based PEC cells and other optoelectronic devices. Graphical Abstract: ga1 Highlights: Colloidal core/shell CdS/CdSe QDs were synthesized and their band alignment were engineered by tuning shell thickness. Optimal PEC device reveals a high photocurrent density of ~ 16.0 mA/cm 2 and significantly improved long-term stability. Theoretical calculation shows that band alignments in this system can be engineered from quasi type-II to inverted type-I. The improved PEC performance is attributed to more favorable light harvesting and photoelectron transport.